2014
DOI: 10.1016/j.vetpar.2014.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Commercial formulation of Metarhizium anisopliae for the control of Rhipicephalus microplus in a pen study

Abstract: The present study evaluated, for the first time, the effect of the commercial formulation Metarril(®) SP Organic of Metarhizium anisopliae plus 10% mineral oil to control Rhipicephalus microplus in a pen study. Three groups were formed with six animals each: the first group was exposed to Metarril(®) plus 10% mineral oil and 1% Tween 80; the second group was exposed to sterile distilled water, mineral oil and Tween 80 (oil control group); and the third group received no treatment (control group). The fungal fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 21 publications
1
17
0
3
Order By: Relevance
“…Through establishing an ideal number of treatment baths for cattle using fungal formulations, and an ideal interval between treatments, it ought to be possible to increase the efficacy of the product and maintain the tick population at an acceptable level. In assessing the product Metarril SP Organic plus mineral oil against cattle ticks in a pen study, Camargo et al (2014) observed average efficacy of 47.74% from a single treatment applied to the animals. In the present study, the same fungal formulation was used, in field tests comprising two treatments applied to cattle, and average efficacy of 75.09% was achieved.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Through establishing an ideal number of treatment baths for cattle using fungal formulations, and an ideal interval between treatments, it ought to be possible to increase the efficacy of the product and maintain the tick population at an acceptable level. In assessing the product Metarril SP Organic plus mineral oil against cattle ticks in a pen study, Camargo et al (2014) observed average efficacy of 47.74% from a single treatment applied to the animals. In the present study, the same fungal formulation was used, in field tests comprising two treatments applied to cattle, and average efficacy of 75.09% was achieved.…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in the average number of ticks on the cattle in the Oil Control group, compared with the animals in the Control group, was observed in this study. Deleterious effects on ticks caused by different oils had previously been reported (Camargo et al, 2012(Camargo et al, , 2014Samish et al, 2014). It is believed that the oils interfere with the physiology of arthropods, through penetrating into tissues and causing cell death, locomotor disability and dehydration (Najar-Rodríguez et al, 2008), and also through interfering in the breathing of the arthropods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EPF is applied in insect pest management as mycoinsecticides; a type of insecticide containing live fungi (Usta, ). B. bassiana and Metarhizium anisopliae are well‐studied EPFs that have been formulated and commercialized as mycoinsecticides known as Botanigard® (http://www.bioworksinc.com) and Metarril ® (Camargo et al, ), respectively. Furthermore, toxic secondary metabolites such as detruxins, beauvericin, and bassiacridin isolated from EPF showed promising results for the incorporation into pesticide formulations (Butt, Coates, Dubovskiy, & Ratcliffe, ; Samuels et al, ).…”
Section: Proteomics In Epfmentioning
confidence: 99%
“…Pests such as locusts, grasshoppers, termites, and cattle ticks have caused huge economic and agricultural losses in many parts of the world such as China, Japan, Australia, Malaysia, Africa, Brazil, and Mexico [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. Vectors of malaria, dengue, and Bancroftian filariasis , which are Aedes spp., Anopheles spp., and Culex spp.…”
Section: Introductionmentioning
confidence: 99%